Ecological education of preschool children: the definitiveconceptual essence of the problem - Nadiia Kravets (Vasyl Stefanyk Precarpathian National University, 2017)
The essence of the concepts of "environmental education", "ecological culture","environmental consciousness", "environmental knowledge", "ecological representation,""emotionally valuable relations", "environmentally appropriate behavior" are analized in thearticle.It was concluded that environmental education is a multifaceted process learning of thaenvironmental knowledge with his usual practical focus, in which exceptional importance isthe adequate perception and awareness of each pupil contents of the main components ofenvironmental education, considering the key to successfully solving its problems. Key words: environmental education, pre-school children.